Re-defining Rape Law: Need of Gender Responsive Justice in Nepal - Bakhadyo, Laxmi (Kathmandu School of Law Review, 2025)
Rape is a persuasive problem in all societies around the world. Non-consensual sexual relationship has been categorized as one of the most heinous crimes in Nepal. Nepali Criminal law has classified gravity of the offence of rape as per the age of the victim and relationship status of perpetrator and victim. Although a landmark leap had been initiated in Nepali laws in the avenues of gender justice and gender equality, Nepali legislations still lack gender responsive justice mechanisms to victims of rape. Law has yet not thought that victim of sexual offence could be beyond females. Nepal is one of the pioneer countries to provide equal rights to the gender and sexual minority community, yet it still classifies their sexual relationships as unnatural sex, and a non-consensual relationship between them is considered an unnatural sexual offence, not rape. In the same way, statutory rape is considered a strict liability, and the legal provisions mandate punishments to underaged boy when both the perpetrator and victim are minors and were in a consensual romantic relationship. This research, based on secondary sources of data, locates that there is an ardent need of redefining rape laws and the need to include gender neutral provisions. Legislatures need to enact laws in such a way that males and sexual/gender minority as victims of rape, marital rape, child sexual offence and rape in conflict be incorporated and designated within the status of victims of rape.